Thyroid Dysfunction in Patients with Liver Disease (Academia Journal of Medicine, 2019)
Background: Liver disease related to alcohol (Ethanol, ethylalcohol) is very common global problem and is one of the major medical  complications of alcohol abuse. Daily consumption is usual for causation of liver disease. Aim: To estimate the prevalence of thyroid  dysfunction in patients with liver disease. Subjects and Methods: Early morning fasting serum thyroid stimulating hormone (TSH), serum  total free thyroxine (FT4) and free triiodothyronine (FT3) was measured by radioimmunoassays in 100 index patients with liver cirrhosis who  did not have history of thyroid diseases. Study Period: November 2018 to October 2019 The age of study population was in the range of 25- 65 years. Out of 100 patients, 75 were males and 25 were females. Conclusion: Abnormalities in circulating thyroid hormone concentrations  i.e hypothyroidism is noted especially in those with ethanol related liver cirrhosis and it is associated with more advanced liver disease.
Keywords: Liver cirrhosis; Hypothyroidism; Ethanol related liver disease; Hepatitis B related liver disease; CTP score